Aspectos gerais das provas no processo do trabalho com enfoque na prova pericial e depósito de honorários do perito - Rosa, Margareth Lopes (2006)
The present dissertation demonstrates the importance of the evidence of the Labor process, generality, origin, concept, principle, onus of evidence and licit ways of evidence. The evidence is very much important and gives the judge enough subsidies to make the decision about the dispute. In order to understand the importance of the evidence in a better way it will be discussed About the concept, principle, the evidende principles, as Well as the onus of evidence in the Processual Law of Brazilian Labor. The objective of dissertation is to analyze the specialit in evidence, as well as his honorary, however, it was not possible to talk about the specialist in evidence without mentioning the ways os evidence, such as: personal testimony, testimonial evidence and documental evidence. The specialist in evidence is necessary when the judge has to technical or specific experience to evaluate the fact. Some examples are: insalubrity and danger. As it is know, there are many books about this topic, however, there is no reasonoble solution when the question is the honoraray of the specialist of the Labor Justice. This is the subject presented in the dissertation. There was no intention to drain the subject, but we believe, to have given a small contribution to the topic. It is a sure thing there will be much discussion to be able to find a solution to make everybody satisfied, once it is such a controversial subject